What works and why? Understanding successful technology enabled learning within institutional contexts : final report : Part A. - Selwyn, Neil; Henderson, Michael; Finger, Glenn; Larkin, Kevin; Smart, Vicky; Chao, Shu-Hua (Office for Learning and Teaching, 2016)
Final report from a project that researched digital technology products, processes and practices that can be realistically developed across the Australian university sector to enhance student learning and the student experience of higher education. The project involved in-depth analysis of three Australian universities - using surveys, interviews and case-studies of ''promising practices' to identify and evaluate proven uses of technology for student outcomes. The project addressed the following challenges a) what is the current impact of digital technology on the student experience and student learning outcomes? b) why are some forms of technology enabled learning successful? c) how can student learning outcomes be technologically-enhanced on a widespread and sustained basis in the near future? The project was designed to inform systemic change in terms of technology use for learning and teaching.